Cleavage and Activation of the Severe Acute Respiratory Syndrome Coronavirus Spike Protein by Human Airway Trypsin-Like Protease - Bertram, S; Glowacka, I; Müller, M; Lavender, H; Gnirss, K; Nehlmeier, I; Niemeyer, D; He, Y; Simmons, G; Drosten, C; Soilleux, E; Jahn, O; et al. (American Society for Microbiology, 2011)
The highly pathogenic severe acute respiratory syndrome coronavirus (SARS-CoV) poses a constant threat to human health. The viral spike protein (SARS-S) mediates host cell entry and is a potential target for antiviral intervention. Activation of SARS-S by host cell proteases is essential for SARS-CoV infectivity, but remains incompletely understood. Here, we analyzed the role of type II transmembrane serine proteases (TTSPs) HAT and TMPRSS2 in SARS-S activation. We found that HAT activates SARS-S in the context of surrogate systems and authentic SARS-CoV infection and is coexpressed with the viral receptor, ACE2, in bronchial epithelial cells and pneumocytes. HAT cleaved SARS-S at R667, as determined by mutagenesis and mass spectrometry, and activated SARS-S for cell-cell fusion in cis and trans, while the related pulmonary protease TMPRSS2 cleaved SARS-S at multiple sites and activated SARS-S only in trans. However, TMPRSS2 but not HAT expression rendered SARS-S-driven virus-cell fusion independent of cathepsin activity, indicating that HAT and TMPRSS2 activate SARS-S differentially. Collectively, our results show that HAT cleaves and activates SARS-S and might support viral spread in patients.